Annual Plan 2010-11 Volume-I (Write-Up) Government of Punjab - Planning Commission (Planning Commission, 2010)
Punjab entered the Eleventh Five Year Plan after a sluggish performance in the Tenth Plan period. the economy of Punjab grew at an annual average growth rate of 5.11% consistently under-performing against the national average of 7.80% during the 10th plan. The 11th plan targets of growth for the State were fixed at 5.90% against the target of 9% for the country. The economic growth in the State was estimated to be 6.88% and 6.40% during 2007- 08 and 2008-09 respectively. the advanced estimates for 2009-10 project a growth rate of 6.69% against the national growth rate of 7.17%. Record procurement of food grains and the tertiary sector has mainly contributed to this high growth.
Government of Punjab Department of Planning